2009
DOI: 10.1007/s00256-009-0699-5
|View full text |Cite
|
Sign up to set email alerts
|

Focal lesions of the patella

Abstract: Focal lesions of the patella may be identified during the investigation of anterior knee pain or as an incidental finding on radiological images. This pictorial review describes the radiographic appearances of a wide range of conditions that have been seen in this sesamoid bone. Where appropriate, computed tomography and magnetic resonance features have been included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Patellofemoral joint disorders represent a common cause of anterior knee pain [1, 2]. As the largest sesamoid bone of the body, the patella functions to magnify the moment arm of the patellar tendon; thereby increasing the effectiveness of extensor musculature [3].…”
Section: Introductionmentioning
confidence: 99%
“…Patellofemoral joint disorders represent a common cause of anterior knee pain [1, 2]. As the largest sesamoid bone of the body, the patella functions to magnify the moment arm of the patellar tendon; thereby increasing the effectiveness of extensor musculature [3].…”
Section: Introductionmentioning
confidence: 99%
“…8 Its characteristic location in the superolateral aspect of the patella allows for accurate diagnosis. The etiology of the patellar dorsal defect is not defi nitely known, although proposed etiologies include incomplete fusion of multiple patellar ossifi cation centers in the general spectrum of multipartite and bipartite patellae, or perhaps an acquired lesion owing to stress-related traction from the vastus lateralis muscle.…”
Section: Mimicker: Femoral Condyle Secondary Ossifi Cationmentioning
confidence: 99%
“…Dear Editors, Many books and articles, including the recent review article in Skeletal Radiology [1], have referred to, and even purportedly shown [2], periosteum of the patella and periosteal reaction of the patella. However, the nature of growth of the patella (as well as carpal bones and tarsal bones, for example) implies that any fibers adjacent to the patella and similar bones are not periosteum.…”
mentioning
confidence: 99%
“…Hedayati and Saifuddin [1] refer to the patellar sleeve fracture as rapid muscle contraction resulting in a "sleeve" of periosteum being pulled off the patella. However, The magnetic resonance (MR) imaging study by Bates et al [4] clearly demonstrates in three children that the sleeve is of cartilage, not periosteum.…”
mentioning
confidence: 99%
See 1 more Smart Citation